FAKTOR-FAKTOR YANG MEMPENGARUHI PRICE EARNING RATIO (PER) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Andika, Avinia; Yuli Chomsatu; Anita Wijayanti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This research aims to find out the effect of financial performance on the PriceEarning Ratio (PER). The population of this study was 123 manufacturingcompanies registered with the IDX in 2016-2018, using purposive samplingtechniques so that a sample of 41 companies was obtained. The data analysis methodused in this study is multiple linear regression analysis. Based on the results of thestudy explained that Debt to Equity Ratio (DER), Price Book Value (PBV), CompanySize (SIZE), and Return on Equity (ROE), affect the Price Earning Ratio (PER),while the Current Ratio (CR) and Total Asset Turnover (TATO), have no effect onthe Price Earning Ratio (PER) in manufacturing companies listed on the IDX.